2013
DOI: 10.1183/09031936.00075712
|View full text |Cite
|
Sign up to set email alerts
|

Sample sizes for clinical trials using sputum eosinophils as a primary outcome

Abstract: Clinical trials do not report sputum eosinophil data in a consistent method and this makes it difficult to compare across studies and to evaluate the sample sizes estimated in these studies. The objectives of the paper are: 1) to systematically review reporting of effect size and sample calculations in randomised controlled trials using sputum eosinophil count as a primary outcome and 2) to illustrate sample size estimation under different methods of data representation using data from an effective anti-eosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The spotlight is now firmly on clinical trial design in airway diseases and how to identify disease subtypes for testing new therapies. An article by DASGUPTA et al [4], in this issue of the European Respiratory Journal, addresses this issue by reporting a systematic review of the use of one biomarker, sputum eosinophils, in randomised controlled trials over the past 10 years, and assesses the implications for study design, analysis and sample size in particular.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The spotlight is now firmly on clinical trial design in airway diseases and how to identify disease subtypes for testing new therapies. An article by DASGUPTA et al [4], in this issue of the European Respiratory Journal, addresses this issue by reporting a systematic review of the use of one biomarker, sputum eosinophils, in randomised controlled trials over the past 10 years, and assesses the implications for study design, analysis and sample size in particular.…”
mentioning
confidence: 99%
“…subject selection, and secondly, in measuring the drug effect. The article by DASGUPTA et al [4] addresses the second of these issues. Their systematic literature review identified 20 randomised controlled trials in asthma and COPD over the past decade that used sputum eosinophils as an outcome measurement.…”
mentioning
confidence: 99%
See 3 more Smart Citations